Convergent? Minds? Some questions about mental evolution. Issue 3 (6th June 2017) - Cartmill, Matt
Abstract : In investigating convergent minds, we need to be sure that the things we are looking at are both minds and convergent. In determining whether a shared character state represents a convergence between two organisms, we must know the wider distribution and primitive state of that character so that we can map that character and its state transitions onto a phylogenetic tree. When we do this, some apparently primitive shared traits may prove to represent convergent losses of cognitive capacities. To avoid having to talk about the minds of plants and paramecia, we need to go beyond assessments of behaviourally defined cognition to ask questions about mind in the primary sense of the word, defined by the presence of mental events and consciousness. These phenomena depend upon the possession of brains of adequate size and centralized ontogeny and organization. They are probably limited to vertebrates. Recent discoveries suggest that consciousness is adaptively valuable as a late error-detection mechanism in the initiation of action, and point to experimental techniques for assessing its presence or absence in non-human mammals.